2022
DOI: 10.2147/jir.s350609
|View full text |Cite
|
Sign up to set email alerts
|

Elevated ALCAM Expression Associated with Endotypes and Postoperative Recurrence in Chronic Rhinosinusitis with Nasal Polyps

Abstract: Background: Chronic rhinosinusitis with polyps (CRSwNP) is characterized by high heterogeneity and postoperative recurrence rate. This study aimed to explore the clinical significance of activated leukocyte cell adhesion molecule (ALCAM) in endotyping CRSwNP and predicting its recurrence. Methods: We recruited 120 CRSwNP patients including 70 non-eosinophilic CRSwNP (neCRSwNP) and 50 eosinophilic CRSwNP (eCRSwNP) patients, and 40 healthy controls (HCs). Serum and tissue samples were collected. Serum ALCAM leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Its diagnosis primarily relies on pathological tissue section examination and eosinophil count, which is invasive and subject to certain subjectivity. 34 , 35 Although previous studies have identified several potential biomarkers for predicting eCRSwNP, such as serum metabolomics, 36 nasal microbiota, 37 and the peripheral blood lymphocyte-to-eosinophil ratio, 38 their sensitivity and specificity remain relatively constrained, hindering their adoption in clinical settings. Therefore, the exploration of objective biomarkers for eCRSwNP is still a current research focus, which will contribute to achieving personalized precision treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Its diagnosis primarily relies on pathological tissue section examination and eosinophil count, which is invasive and subject to certain subjectivity. 34 , 35 Although previous studies have identified several potential biomarkers for predicting eCRSwNP, such as serum metabolomics, 36 nasal microbiota, 37 and the peripheral blood lymphocyte-to-eosinophil ratio, 38 their sensitivity and specificity remain relatively constrained, hindering their adoption in clinical settings. Therefore, the exploration of objective biomarkers for eCRSwNP is still a current research focus, which will contribute to achieving personalized precision treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, although surgical treatment is one of the effective treatment modalities to improve clinical symptoms in patients with CRSwNP, not all patients achieve good prognoses due to its uncertain etiology and high disease heterogeneity [ 31 ]. It was well established that the degree of eosinophil infiltration and type 2 inflammation in the mucosa profoundly influenced the risk of CRSwNP recurrence after surgery [ [32] , [33] , [34] ].In the present study, we found that serum and tissue S100A8 levels were significantly upregulated in patients with recurrent CRSwNP compared to patients with primary CRSwNP. Moreover, serum S100A8 levels were positively correlated with peripheral blood and tissue eosinophil percentages.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, exploring risk factors associated with CRSwNP recurrence and predicting its recurrence are extremely challenging and urgently needed for rhinologists. Although several variables and indicators were reported to be correlated with postoperative recurrence, including accompanied asthma [10], Charcot-Leyden crystal [40] and peripheral parameters [41], and activated leukocyte cell adhesion molecule [42], there was no reliable biomarker available in clinical practice. Here, we firstly found that BAFF expressions were significantly enhanced in recurrent CRSwNP patients, and serum levels were closely linked with the rate of CRSwNP postoperative recurrence.…”
Section: Discussionmentioning
confidence: 99%